Jan Gehl - Matan, Annie (SAGE, 2017)
Key Thinkers on Cities provides an engaging introduction to the dynamic intellectual field of urban studies. It profiles the work of 40 innovative thinkers who represent the broad reach of contemporary urban scholarship and whose ideas have shaped the way cities around the world are understood, researched, debated and acted upon. Providing a synoptic overview that spans a wide range of academic and professional disciplines, theoretical perspectives and methodological approaches, the entry for each key thinker comprises: A succinct introduction and overview Intellectual biography and research focus An explication of key ideas Contributions to urban studies The book offers a fresh look at well-known thinkers who have been foundational to urban scholarship, including Jane Jacobs, Henri Lefebvre, Manuel Castells and David Harvey. It also incorporates those who have helped to bring a concern for cities to more widespread audiences, such as Jan Gehl, Mike Davis and Enrique Peñalosa. Notably, the book also includes a range of thinkers who have more recently begun to shape the study of cities through engagements with art, architecture, computer modelling, ethnography, public health, post-colonial theory and more. With an introduction that provides a mapping of the current transdisciplinary field, and individual entries by those currently involved in cutting edge urban research in the Global North and South, this book promises to be an essential text for anyone interested in the study of cities and urban life. It will be of use to those in the fields of anthropology, economics, geography, sociology and urban planning.